EFFECTIVENESS E-HEALTH TO SELF MANAGEMENT OF DIABETES MELLITUS TYPE 2 : LITERATURE REVIEW - Siti Hardiyanti; Firnanda Erindia; Sigit Mulyono; Achsan Tudhonny; Umdatus Soleha (Indonesian Journal of Community Health Nursing, 2022)
Introduction: Patient and nurse is constructive relationship beneficial in a self-management support approach. Research shows e-health intervention has the potential to support self-management for adults with type 2 diabetes. The purpose this article to apply the application of e-health to people with type 2 diabetes mellitus. Method: Method is search journal articles through basic data in ProQuest, Clinical key, EBSCO with a time span of 2018-2022, using the keywords "e-health intervention" and "diabetes mellitus type 2". The number of related articles is 10 journals. Results: Results the literature review conducted showed that e-health has an effective and efficient impact on self-management in patients with type 2 diabetes mellitus, nurses can find time to find out the progress of people with diabetes mellitus, reduce the incidence of diabetes and complications. Conclusion: Conclusion the use of e-health in self-management of people with diabetes mellitus has provided positive benefits for the development and improvement of service quality for the community. Health is a new medium in health services that requires broader knowledge and more in-depth practice, so the use of digital media in management needs to conduct further research  in the focus of research on health.   Keywords: e-health, self-management, diabetes mellitus.